President Truman and the atomic bomb : opposing viewpoints - O'Neal, Michael, 1949- (San Diego, Calif. : Greenhaven Press, 1990)
Discusses the events and decisions that led to the bombing of Hiroshima in 1945, particularly Truman's role as decision maker and initiator of the act.
Includes bibliographical references (p. 106-107) and index.
Keywords: Truman, Harry S., -- 1884-1972 -- Military leadership -- Juvenile literature; Truman, Harry S., -- 1884-1972.; Atomic bomb -- History -- Juvenile literature; Atomic bomb -- History; Hiroshima-shi (Japan) -- History -- Bombardment, 1945 -- Juvenile literature; Hiroshima-shi (Japan) -- History -- Bombardment, 1945.